Relevant aspects of the organizational culture of teachers in a Peruvian technological higher education institution - Calderón-Fuentes, Edwin Humberto (2023)
This article analyzes the current and desired organizational culture in a technological higher education institution in Peru based on the perceptions of its teachers. Organizational culture is an essential intangible corporate asset as it helps explain the underlying aspects that significantly impact the management of organizations. For this reason, we diagnosed the attributes of the organizational culture in the aforementioned educational institution to support the definition of actions that promote its organic corporate development, attending to the needs of its environment. We used quantitative methodology to collect information from questionnaires based on the Competing Values Framework and the Organizational Culture Assessment Instrument, which allowed us to identify relevant characteristics of each type of organizational culture. The findings of the surveys applied to the teachers revealed and validated that the current dominant culture is hierarchical and, in a second instance, clan culture. Educators would expect market culture to predominate without abandoning hierarchical and clan cultures. This research is useful because it offers the institution's educational management staff detailed knowledge about the main characteristics of its organizational culture and the understanding of the context in which it occurs. It also helps determine how well organizational culture and strategic corporate objectives align and, if applicable, define the opportunities for improvement and the actions required to continue enriching the organizational culture.